SISTEM PERBANKAN DALAM NEGARA KESEJATERAAN DI INDONESIA - Hendri Jayadi Pandiangan (Fakultas Hukum Universitas Kristen Indonesia, 2018)
Abstract The banking system in Indonesia is regulated in Law No.7 of 1992 (amended by Law No.10 of 1998). The development of banking shows the dynamics in economic life. The banking sector in the life of a country is an agent of development, because banks are nancial institutions that have the function as nancial intermediary institutions, namely as institutions that collect funds from the public in the form of deposits and channel them back to the public in the form of credit or nancing. Banking is also an agent of trust, bearing in mind that there is one principle of bank management, the duciary principle. The provisions of Article 4 of Act Number 7 of 1992 concerning Banking as amended by Act Number 10 of 1998 states that Indonesian banks aim to support the implementation of national development in order to improve equity, economic growth, and national stability towards improving the welfare of the people at large. Keyword:banking system; development; economic growth.